URBAN NETWORK CHARACTERIZATION OF FUNCTIONAL PLANNINGREGION NINE OF THE STATE OF RIO GRANDE DO SUL - Martins, Marcele Salles; Saugo, Andréia (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
In recent decades, changes occurred in the urban landscape of Brazilian cities, caused mainly by the growth of urbanization, driving changes in the profile of the urban population. Accordingly, this article presents a diagnosis of the urban network of Functional Planning Region Nine formed by 130 municipalities located in the north of Rio Grande do Sul, in the period 1985 to 2007. The methodological approach initiated by the organization of the database of indicators, based on official sources. It was found that the urban network is formed by a majority of municipalities with population up to 5,000 inhabitants, concentrated in rural areas. The economic participation is based on service activity.